Smart agriculture with internet of things in cornfields. (March 2021) - Cicioğlu, Murtaza; Çalhan, Ali
Highlights: Large-scale cornfields can be monitored with different sensors for irrigation, insect and pest detection, crop status, fertilization, soil preparations, etc. Various IoT capabilities are used for smart agriculture activities. Ten different specifications about cornfields are monitored on Grafana. CSMA/CA-based wireless network is proposed for each acre of cornfield. Drone assisted data gathering process is also developed for large-scale cornfields. InfluxDB, Node-Red, Grafana, etc. utilities are used for surveillance system. Abstract: This paper aims to achieve productive corn harvest in large-scale fields with the help of Internet of Things hardware and software facilities. The system uses heterogeneous sensor nodes which are capable of sensing acoustic, rain, wind, light, temperature and pH levels of the cornfields for smart agriculture applications. The specific properties of the cornfields are gathered with special purpose sensors at coordinator nodes, and then the coordinator node sends the data to the Drone as a relay node. It is sufficient for the sensor nodes to detect conditions at specific times of the day because the data in the cornfields does not change rapidly. The Drone provides data to the base stations for monitoring on farmers' visual devices. Therefore, the necessity of long distance communication between sensors in a region of large-scale cornfields is eliminated. Graphical abstract: Image, graphical abstract